Phubbing By Gen-Z And Gen-Y: Exploring Smartphone Usage And Its Implications On Interpersonal Communication In The Workplace - Bonifacius Sandro Dwi Atmaja; Silvanus Alvin (Jurnal Indonesia Sosial Teknologi, 2023)
This research examines "phubbing" behavior among Gen-Z and Gen-Y employees at PT Siloam International Hospitals, Indonesia. Phubbing refers to the act of using smartphones while in the presence of others, diverting attention from face-to-face interactions. The study employs a qualitative case study approach, interviewing six participants selected through purposive sampling. Findings reveal a hybrid work system at Siloam, with a mix of face-to-face and virtual communication. Smartphones and laptops play vital roles in work-related communication, with some participants using smartphones for 80-90% of their work hours. Urgency, multitasking, and avoidance of certain topics are cited as reasons for phubbing. Understanding these drivers can help organizations address communication challenges and foster attentive interactions. Promoting mindful smartphone usage can lead to improved workplace dynamics and productivity, emphasizing the importance of empathy and open communication.